2012
DOI: 10.1161/circep.112.970491
|View full text |Cite
|
Sign up to set email alerts
|

Repolarization Changes Underlying Long-Term Cardiac Memory Due to Right Ventricular Pacing

Abstract: Background Cardiac memory refers to the observation that altered cardiac electrical activation results in repolarization changes that persist after the restoration of a normal activation pattern. Animal studies, however, have yielded disparate conclusions both regarding the spatial pattern of repolarization changes in cardiac memory and the underlying mechanisms. This study was undertaken to produce three dimensional images of the repolarization changes underlying long-term cardiac memory in humans. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 34 publications
1
32
0
2
Order By: Relevance
“…16,19 Later, it was discovered that not only the transmural repolarization gradient in CM is site-specific, 20 but also other gradients exist including apical-basal and right-to-left ventricle. 21,22 There is a general agreement across the studies that CM is associated with prolongation of repolarization in the early activated areas. However, repolarization changes at the late activated sites were variable ranging from shortening, 23 minimal, or no change 20,22 to significant APD prolongation.…”
Section: Electrophysiology Molecular Mechanisms and Triggers Of CM mentioning
confidence: 91%
See 1 more Smart Citation
“…16,19 Later, it was discovered that not only the transmural repolarization gradient in CM is site-specific, 20 but also other gradients exist including apical-basal and right-to-left ventricle. 21,22 There is a general agreement across the studies that CM is associated with prolongation of repolarization in the early activated areas. However, repolarization changes at the late activated sites were variable ranging from shortening, 23 minimal, or no change 20,22 to significant APD prolongation.…”
Section: Electrophysiology Molecular Mechanisms and Triggers Of CM mentioning
confidence: 91%
“…21,22 There is a general agreement across the studies that CM is associated with prolongation of repolarization in the early activated areas. However, repolarization changes at the late activated sites were variable ranging from shortening, 23 minimal, or no change 20,22 to significant APD prolongation. 24,25 Discrepancy in these findings is a subject of an ongoing debate and is likely related to the differences in experimental models, pacing site, species, and methods of measurement.…”
Section: Electrophysiology Molecular Mechanisms and Triggers Of CM mentioning
confidence: 91%
“…12 (2) In patients implanted with dual chamber pacemakers because of sinus node dysfunction, reprogramming the devices to atrial pacing only, after weeks of continuous atrioventricular pacing, leads to marked QT prolongation, 21 and electrocardiographic imaging 22 confirms that (like in the animal model) cardiac memory in humans is associated with increased dispersion of repolarization across the ventricles. In all these studies, the impact of cardiac memory on QT prolongation was modest and would not be expected to be arrhythmogenic.…”
Section: Arrhythmogenic Potential Of Cardiac Memorymentioning
confidence: 96%
“…Of note, in normal hearts undergoing abnormal activation such as RV apex pacing, intermittent LBBB or preexcitation the presence of cardiac memory has traditionally been associated with proarrhythmia and worse prognosis [14]. Marrus et al showed that in patients displaying cardiac memory, cessation of ventricular pacing results in the prolongation of the action potential (APD) of the myocytes closest to the site of pacing [6]. This increases dispersion of repolarization which in turn is known to promote arrhythmia [15].…”
Section: Qrs and T Vector Changes As Witnesses Of Subtle Electrical Rmentioning
confidence: 99%
“…Cardiac memory is defined as temporarily persisting changes of the T-wave axis when normal cardiac excitation is restored after a period of abnormal cardiac activation [2]. This phenomenon has been described following right ventricular pacing, cardiac resynchronization therapy, intermittent left bundle branch block, ventricular and supraventricular tachycardia or pre-excitation [3][4][5][6]. Electrical remodeling is the name for a range of ECG changes that accompany ventricular remodeling but do not fit within the strict definition of cardiac memory, such as changes in QRS complex duration or QRS vector angles.…”
Section: Introductionmentioning
confidence: 99%